Analisis Faktor-Faktor Penghambat dan Tantangan Utama Bisnis: Studi Kasus pada Usaha Jeruk Salit di Kabanjahe - Andi Cici Thania; Marito Ritonga; Fadli Agus Triansyah; Sakina Balqis; Ema Paskah Riyanthi BR Sinuhaji; Gusti Alinski Tumanggor (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2026)
Small and medium-sized enterprises in the agricultural sector face various complex challenges in maintaining sustainability and increasing their competitiveness in a dynamic market. This study aims to identify and analyze the inhibiting factors and main challenges faced by the Jeruk Salit business in Kabanjahe. The research method uses a qualitative approach with in-depth interviews with orange farm owners to explore information about operations, production management, and challenges faced in running the business. The findings show that the Salit Orange business faces several significant obstacles, including limited harvest season (only once a year), uncertainty in production volume, fruit fly infestation, limited product shelf life (only two weeks), wasteful use of orange waste, and lack of competitive product differentiation. In addition, the study also found that government support is still minimal and farmers have limited knowledge about waste management and modern agricultural technology. The implications of this study are the need for a comprehensive business development strategy, including product diversification through waste processing, the development of agritourism models, collaboration between farmers, and more responsive government policies to the needs of small farmers in order to improve the sustainability and competitiveness of the citrus business in Kabanjahe.